TRANSFOR MASI TENAGA PENGAJAR KE ARAH DOSEN BERSERTIFIKASI PENDIDIK: ANALISIS DESKRIPTIF DENGAN REGRESI LOGISTIK - R, Ratiyah (Politeknik Negeri Jakarta, 2018)
ABSTRACT Account Vol 5 No 2: Ratiyah MASI TENAGA PENGAJAR KE ARAH DOSENBERSERTIFIKASI PENDIDIK: ANALISIS DESKRIPTIF Data from LAKIP 2015-2016 indicates the decreasing number of lecturers receiving Educator Certification inKopertis III, 786 in 2015 and 650 lecturers in 2016, but this is not a guarantee of decreasing the ability and interestof lecturers to take care of Academic Functional Position and Educator Certification. The quality of a lecturergreatly affects the fluency of Teaching and Learning Activities in every university. Information on thecharacteristics of Teachers in Kopertis III, as well as the relationship as well as the tendency between thecharacteristics possessed by the decision to take care of the Academic Functional Position is expected to assistDIKTI in formulating policies on lecturers. This research utilizes excess data of LAKIP data from Kopertis 3,where data is analyzed to know the tendency of lecturers characteristic to interest in managing AcademicFunctional Position and Educator Certification. Based on the results of descriptive analysis, it is known that atthis time the transformation of workers towards the certification of educators is running. This is indicated by anincrease in the number of lecturers who have Academic Functional Position. Nevertheless, the number of lecturerstaking the certification exam and the increasing difficulty of qualification of educator certification slightlyhindered the transformation process. Furthermore, logistic regression analysis shows that older lecturers have atendency to be reluctant to take care of Functional Positions and Educator Certification. Apparently, the economicneeds of married workers do not contribute significantly in their decision to take care of Academic FunctionalPosition and Educator Certification.Keywords: lecturer, Academic Functional Position, Educator Certification, transformation. ABSTRAK DENGAN REGRESI LOGISTIK Ratiyah. Data LAKIP 2015-2016 menunjukkan menurunya jumlah dosen yang mendapatkan Sertifikasi Pendidikdi Kopertis III, yaitu 786 di tahun 2015 dan 650 dosen di tahun 2016, namun hal ini bukan merupakanjaminan menurunya kemampuan dan minat dosen untuk mengurus Jabatan Fungsional Akademik danSertifikasi Pendidik. Kualitas seorang Tenaga Pengajar sangat mempengaruhi kelancaran KegiatanBelajar Mengajar di setiap Perguruan Tinggi. Informasi mengenai karakteristik Tenaga Pengajar diKopertis III, serta hubungan sekaligus kecenderungan antara karakteristik yang dimiliki dengankeputusannya untuk mengurus Jabatan Fungsional Akademik diharapkan dapat membantu DIKTIdalam merumuskan kebijakan mengenai dosen. Penelitian ini memanfaatkan kelebihan data LAKIP darikopertis 3, dimana data dianalisis untuk mengetahui kecenderungan karakteristik dosen terhadap minatmengurus Jabatan Fungsional Akademik dan Sertifikasi Pendidik. Berdasarkan hasil analisis deskriptifdiketahui bahwa pada saat ini transformasi tenaga pengajar ke arah dosen bersertifikasi pendidik tengahberjalan. Ini ditunjukkan dengan peningkatan jumlah dosen yang memiliki Jabatan Fungsional Akademik.Namun demikian, banyaknya jumlah dosen yang mengikuti ujian sertifikasi dan semakin sulitnya kualifikasi sertifikasipendidik sedikit menghambat proses transformasi tersebut. Lebih lanjut, analisis regresi logistik menunjukkanbahwa dosen yang usianya lebih tua mempunyai kecenderungan untuk mengurus Jabatan Fungsional dan SertifikasiPendidik.. Ternyata, kebutuhan ekonomi pekerja yang telah menikah tidak memberikan kontribusi yangsignifikan dalam keputusannya untuk mengurus Jabatan Fungsional Akademik dan Sertifikasi Pendidik. Kata kunci: dosen, Jabatan Fungsional Akademik, Sertifikasi Pendidik, transformasi